Solar cell and solar cell module
By setting a composite TCO layer with a multi-layer structure on the surface of the P-type doped microcrystalline silicon layer of the solar cell, the problem of limited efficiency improvement in traditional technology is solved, and higher photoelectric conversion efficiency and battery performance are achieved.
Patent Information
- Application Number
- CN202410141619.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2025-04-18
AI Technical Summary
Traditional heterojunction solar cells have difficulties in improving efficiency, mainly due to the parasitic absorption of incident light by the amorphous silicon layer and the light shading caused by the front metal electrode, resulting in a drop in the short circuit current. At the same time, the back surface emitter and back field of the heterojunction back contact battery are poorly in contact with the transparent conductive oxide layer, resulting in high series resistance.
Using a composite transparent conductive oxide (TCO) layer structure, a multi-layer structure TCO layer is provided on the surface of the P-type doped microcrystalline silicon layer, including the first TCO layer, the second TCO layer and the third TCO layer. By adjusting the thickness and material composition of each layer, the conductive performance of the TCO layer is improved while maintaining optical performance.
By improving the conductivity of the TCO layer, the photoelectric conversion efficiency of solar cells is improved, the problem of limited efficiency improvement in traditional technologies is solved, and the overall performance of the battery is improved.
Smart Images

Figure CN119855290A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic devices, and in particular to a solar cell and a solar cell assembly. Background Art
[0002] Traditional heterojunction solar cells (HJT) have good surface passivation and less recombination, so the open circuit voltage is high, thanks to the chemical passivation of its intrinsic hydrogenated amorphous silicon layer and the field effect passivation of the doped amorphous silicon layer. However, the amorphous silicon layer has strong parasitic absorption of incident light, and the front metal electrode will also cause shading, resulting in a decrease in short-circuit current, which makes it impossible to further improve efficiency. Heterojunction back contact cells (HBC) lay both the emitter and back field on the back of the cell, and only have an intrinsic passivation layer and an anti-reflection layer on the front, which greatly increases the light transmission effect. However, the back emitter, back field and transparent conductive oxide (TCO) layer of the cell have poor contact, resulting in high series resistance. Summary of the invention
[0003] In view of this, the present application provides a solar cell and a solar cell module, wherein the solar cell has a composite TCO layer structure, which improves the conductivity of the TCO while ensuring the optical properties of the TCO layer, thereby obtaining a solar cell with better photoelectric performance.
[0004] In a first aspect, the present application provides a solar cell, the solar cell comprising a back intrinsic hydrogenated amorphous silicon layer and a doped layer arranged in sequence, the doped layer comprising a P-type doped microcrystalline silicon layer and an N-type non-doped layer arranged alternately and spaced apart, the surfaces of the P-type doped microcrystalline silicon layer and the N-type non-doped layer are independently and sequentially stacked with a TCO layer and a metal electrode layer; wherein the TCO layer on the surface of the P-type doped microcrystalline silicon layer is a composite TCO layer, the composite TCO layer comprising a first TCO layer and a second TCO layer. The first TCO layer is close to the P-type doped microcrystalline silicon layer, and the first TCO layer and the second TCO layer have different light transmittance and resistivity.
[0005] Optionally, the light transmittance of the first TCO layer is greater than the light transmittance of the second TCO layer; and the resistivity of the first TCO layer is greater than the resistivity of the second TCO layer.
[0006] Optionally, the thickness of the composite TCO layer is 80-120 nm.
[0007] Optionally, the composite TCO layer further includes a third TCO layer, and the first TCO layer, the second TCO layer and the third TCO layer are stacked in sequence.
[0008] Optionally, the thickness of the first TCO layer is 15-30 nm, the thickness of the second TCO layer is 5-20 nm, and the thickness of the third TCO layer is 30-100 nm.
[0009] Optionally, a thickness ratio of the first TCO layer, the second TCO layer and the third TCO layer is (0.15-1):(0.05-0.67):1.
[0010] Optionally, the light transmittance of the first TCO layer is 85-92%, the light transmittance of the second TCO layer is 80-85%, and the light transmittance of the third TCO layer is 85-92%.
[0011] Optionally, the resistivity of the first TCO layer is (3-5)×10 -3 Ω·cm, the resistivity of the second TCO layer is 8×10 -4 -3×10 -3 Ω·cm, the resistivity of the third TCO layer is (3-5)×10 -3 Ω·cm.
[0012] Optionally, the first TCO layer, the second TCO layer and the third TCO layer independently include one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3.
[0013] Optionally, the first TCO layer and the third TCO layer include SnOx, wherein x is 1.75-1.85; and the second TCO layer includes SnOx, wherein x is 1.6-1.7.
[0014] Optionally, the TCO layer on the surface of the N-type non-doped layer is a fourth TCO layer, and the thickness of the fourth TCO layer is 80-120 nm.
[0015] Optionally, the fourth TCO layer has a light transmittance of 85-92% and a resistivity of (3-5)×10 -3 Ω·cm.
[0016] Optionally, the fourth TCO layer includes one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3.
[0017] Optionally, the fourth TCO layer comprises SnOx, wherein x is 1.75-1.85.
[0018] Optionally, the N-type non-doped layer includes one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3.
[0019] Optionally, the N-type non-doped layer includes SnOx, wherein x is 1.6-1.7.
[0020] Optionally, the solar cell includes a crystalline silicon substrate, which includes a back side and a front side that are relatively arranged, the back side is provided with the back side intrinsic hydrogenated amorphous silicon layer, and the front side is sequentially stacked with a front side velvet surface, a front side intrinsic hydrogenated amorphous silicon layer, and an anti-reflection layer, and the front side velvet surface is close to the front side.
[0021] In a second aspect, the present application provides a solar cell assembly, wherein the solar cell assembly comprises the solar cell described in the first aspect of the present application.
[0022] Through the above technical solution, the present application improves the overall conductivity of the composite TCO layer without affecting the optical performance by setting a composite TCO layer structure on the surface of the P-type doped microcrystalline silicon layer of the solar cell, thereby improving the photoelectric conversion efficiency of the solar cell.
[0023] Other features and advantages of the present application will be described in detail in the subsequent specific implementation section. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 It is a schematic diagram of a partial structure of a solar cell in one embodiment of the present application.
[0026] Figure 2 It is a schematic diagram of the complete structure of a solar cell in one embodiment of the present application.
[0027] Description of reference numerals: 1-crystalline silicon substrate, 2-front velvet surface, 3-front intrinsic hydrogenated amorphous silicon layer, 4-front anti-reflection layer, 5-back intrinsic hydrogenated amorphous silicon layer, 6-P-type doped microcrystalline silicon layer, 7-first TCO layer, 8-second TCO layer, 9-third TCO layer, 10-metal electrode layer, 11-N-type non-doped layer, 12-fourth TCO layer, 13-composite TCO layer. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0029] The term "first" or "second" in the specification and claims of this application may include one or more of the features explicitly or implicitly. In the description of this application, unless otherwise specified, "plurality" means two or more. In addition, "and / or" in the specification and claims means at least one of the connected objects, and the character " / " generally means that the objects connected before and after are in an "or" relationship.
[0030] like Figure 1 As shown, the present application provides a solar cell, the solar cell comprises a back intrinsic hydrogenated amorphous silicon layer 5 and a doping layer arranged in sequence, the doping layer comprises a P-type doped microcrystalline silicon layer 6 and an N-type non-doped layer 11 arranged alternately and spaced apart, the surfaces of the P-type doped microcrystalline silicon layer 6 and the N-type non-doped layer 11 are independently and sequentially stacked with a TCO layer and a metal electrode layer 10; wherein the TCO layer on the surface of the P-type doped microcrystalline silicon layer 6 is a composite TCO layer 13, the composite TCO layer 13 comprises a first TCO layer 7 and a second TCO layer 8. The first TCO layer 7 is close to the P-type doped microcrystalline silicon layer 6, and the first TCO layer 7 and the second TCO layer 8 have different transmittance and resistivity.
[0031] On the one hand, the TCO layer allows light to pass through and enter the absorption layer of the silicon wafer, thereby improving the light absorption efficiency of the battery. On the other hand, it can conduct the collected current and transmit it to the external circuit. In addition, the TCO layer can also reduce charge recombination losses. The performance of the TCO layer has an important influence on the photoelectric performance of solar cells.
[0032] In one embodiment of the present application, the transmittance of the first TCO layer 7 is greater than the transmittance of the second TCO layer 8; the resistivity of the first TCO layer 7 is greater than the resistivity of the second TCO layer 8. The transmittance of the first TCO layer 7 is 85-92%, and the transmittance of the second TCO layer 8 is 80-85%; the resistivity of the first TCO layer is (3-5)×10 -3 Ω·cm, the resistivity of the second TCO layer is 8×10 -4 -3×10 -3 The first TCO layer 7 is in direct contact with the P-type doped microcrystalline silicon layer 6, so the first TCO layer 7 has a higher light transmittance, a higher resistivity and a lower conductivity, which is beneficial to the transport of carriers.
[0033] In one embodiment of the present application, the composite TCO layer 13 also includes a third TCO layer 9, that is, the composite TCO layer 13 includes a three-layer structure, specifically including a first TCO layer 7, a second TCO layer 8 and a third TCO layer 9 stacked in sequence, and the first TCO layer 7 is close to the P-type doped microcrystalline silicon layer 6; that is, the surface of the P-type doped microcrystalline silicon layer 6 is sequentially stacked with the first TCO layer 7, the second TCO layer 8 and the third TCO layer 9. The thickness of the composite TCO layer 13 is 80-120nm, preferably 100-110nm. The thickness of the TCO layer within this range can ensure both optical performance and electrical conductivity. In addition, the three-layer TCO layer further improves the electrical conductivity. In one embodiment of the present application, the thickness of the composite TCO layer 13 is 110nm.
[0034] In one embodiment of the present application, the thickness of the first TCO layer 7 is 15-30 nm, the thickness of the second TCO layer 8 is 5-20 nm, and the thickness of the third TCO layer 9 is 30-100 nm. The ratio of the thickness of the first TCO layer 7, the second TCO layer 8 and the third TCO layer 9 is (0.15-1): (0.05-0.67): 1. The thickness of each layer of the composite TCO layer 13 is set in this way, which is conducive to improving the conductivity without significantly reducing the light transmittance.
[0035] In one embodiment of the present application, the surface of the N-type non-doped layer 11 is sequentially stacked with a fourth TCO layer 12 and a metal electrode layer 10. The thickness of the fourth TCO layer 12 is 80-120 nm, preferably 100-110 nm, and the thickness of the fourth TCO layer 12 should be consistent with the thickness of the composite TCO layer 13, that is, the thickness of the fourth TCO layer 12 is equal to the total thickness of the first TCO layer 7, the second TCO layer 8 and the third TCO layer 9. The thickness of the fourth TCO layer 12 within this range can ensure both optical performance and electrical conductivity.
[0036] In one embodiment of the present application, the transmittance of the first TCO layer 7 is 85-92%, the transmittance of the second TCO layer 8 is 80-85%, and the transmittance of the third TCO layer 9 is 85-92%. The transmittances are all defined under the condition of a wavelength of 400-1100 nm. In addition, the transmittances of the first TCO layer 7 and the third TCO layer 9 located on the outside of the composite TCO layer 13 are relatively high, and the resistivity of the second TCO layer 8 located in the middle is relatively low, which is conducive to improving the carrier concentration of the composite TCO layer 13 without significantly reducing the transmittance.
[0037] In one embodiment of the present application, the resistivity of the first TCO layer is (3-5)×10 -3Ω·cm, the resistivity of the second TCO layer is 8×10 -4 -3×10 -3 Ω·cm, the resistivity of the third TCO layer is (3-5)×10 -3 The second TCO layer 8 in the middle of the composite TCO layer 13 has a lower resistivity, which is beneficial to improving the overall conductive performance of the composite TCO layer 13 .
[0038] In one embodiment of the present application, the fourth TCO layer 12 has a light transmittance of 85-92% and a resistivity of (3-5)×10 -3 Ω·cm. The transmittance here is also limited under the condition of wavelength 400-1100nm. The resistivity of the fourth TCO layer has good conductivity within this range.
[0039] In one embodiment of the present application, the material of the N-type non-doped layer 11 includes one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3, and the material of the fourth TCO layer 12 includes one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3. Preferably, the material of the N-type non-doped layer 11 and the fourth TCO layer 12 is the same, and may preferably be SnOx. In one embodiment of the present application, the N-type non-doped layer 11 and the fourth TCO layer 12 are both SnOx, but the oxygen vacancy content of the two is different. Specifically, the N-type non-doped layer 11 includes SnOx, and x is in the range of 1.6-1.7, and the fourth TCO layer 12 includes SnOx, and x is in the range of 1.75-1.85. Oxygen vacancies refer to the detachment of oxygen atoms in metal oxides to form vacancies. A high oxygen vacancy content means a high carrier concentration and good conductivity, but it will also produce a large parasitic absorption of light; a low oxygen vacancy content indicates that the film is fully oxidized and has good light transmittance, but its conductivity is poor compared to a high content of oxygen vacancies. The N-type non-doped layer 11 in this structure has a low oxygen vacancy content in order to produce a smaller work function, which is conducive to more efficient extraction of electrons. Since the N-type non-doped layer 11 and the fourth TCO layer 12 are made of the same material, the interface contact between the N-type non-doped layer 11 and the fourth TCO layer 12 is effectively improved, the interface resistance is reduced, and the fill factor is improved, thereby further improving the cell efficiency of the solar cell.
[0040] In one embodiment of the present application, the materials of the first TCO layer 7, the second TCO layer 8 and the third TCO layer 9 independently include one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3. Further, SnOx can be preferably selected. The selection of SnOx in the solar cell facilitates the adjustment of the oxygen vacancy content. In one embodiment of the present application, the materials of the first TCO layer 7, the second TCO layer 8 and the third TCO layer 9 are all SnOx, but the oxygen vacancy content is different. Among them, the first TCO layer 7 and the third TCO layer 9 include SnOx, x is in the range of 1.75-1.85, and the second TCO layer 8 includes SnOx, x is in the range of 1.6-1.7. The sputtering target used in the preparation of the three TCO layers is the same, and only the process conditions are different. Specifically, when preparing the first TCO layer 7 and the third TCO layer 9, the oxygen flow rate ratio is larger, the oxygen vacancies are smaller, and the carrier concentration is lower, which can reduce its parasitic absorption of incident light and increase its light transmittance; when preparing the second TCO layer, the oxygen flow rate ratio is smaller, which can produce more oxygen vacancies and generate more carriers, thereby reducing the work function and enhancing its ability to extract carriers.
[0041] In general, the materials of the first TCO layer 7, the second TCO layer 8, the third TCO layer 9, the fourth TCO layer 12 and the N-type non-doped layer 11 are preferably SnOx, except that the oxygen vacancy content of the first TCO layer 7, the third TCO layer 9 and the fourth TCO layer 12 is consistent, and x is in the range of 1.75-1.85; while the oxygen vacancy content of the second TCO layer 8 and the N-type non-doped layer 11 is consistent, and x is in the range of 1.6-1.7. The above structure is conducive to ensuring the overall photoelectric performance of the composite TCO layer 13, and at the same time can reduce the series resistance of the second TCO layer 8 and the N-type non-doped layer 11, improve the conductivity, and thus improve the photoelectric conversion efficiency of the battery.
[0042] The material of the metal electrode generally needs to have the characteristics of high conductivity, weldability, corrosion resistance and stability. In one embodiment of the present application, the material of the metal electrode layer 10 can be a copper electrode or a silver electrode. The above materials can form a good ohmic contact with the TCO layer to ensure the long life of the battery. In one embodiment of the present application, the metal electrode layer 10 is a copper electrode.
[0043] In one embodiment of the present application, the P-type doped microcrystalline silicon layer 6 serves as a hole transport layer, and the N-type non-doped layer serves as an electron transport layer. The thickness of the N-type non-doped layer 11 and the P-type doped microcrystalline silicon layer 6 is consistent, which is 5-20nm, and the ratio of the width of the N-type non-doped layer 11 and the P-type doped microcrystalline silicon layer 6 is 1: (2.8-3.2), preferably 1: 3. Since the P-type doped microcrystalline silicon layer 6 and the N-type non-doped layer 11 in the HBC battery are both arranged on the same surface, the carrier transmission path is lateral transmission. For the N-type silicon substrate, the majority carriers are electrons and the minority carriers are holes. When the P-type doped microcrystalline silicon layer 6 is arranged wider, the holes can move a shorter distance to reach. Therefore, the above structure is conducive to reducing the minority carrier transmission distance, reducing the lateral transmission resistance, and at the same time reducing the minority carrier recombination and improving the passivation.
[0044] In addition, if Figure 2 As shown, the solar cell is a HBC cell, comprising a crystalline silicon substrate 1, wherein the crystalline silicon substrate 1 comprises a back side and a front side arranged oppositely, wherein the back side is provided with the back side intrinsic hydrogenated amorphous silicon layer 5, and the front side is sequentially stacked with a front side velvet 2, a front side intrinsic hydrogenated amorphous silicon layer 3, and an anti-reflection layer 4, wherein the front side velvet 2 is close to the front side; a doped layer is stacked on the surface of the back side intrinsic hydrogenated amorphous silicon layer 5, wherein the doped layer comprises a P-type doped microcrystalline silicon layer 6 and an N-type non-doped layer 11 which are alternately arranged and spaced apart, and a TCO layer and a metal electrode layer 10 are independently and sequentially stacked on the surfaces of the P-type doped microcrystalline silicon layer and the N-type non-doped layer; wherein the TCO layer on the surface of the P-type doped microcrystalline silicon layer 6 is a composite TCO layer 13, and the composite TCO layer 13 has a multilayer structure, comprising a first TCO layer 7, a second TCO layer 8, and a third TCO layer 9; and the TCO layer on the surface of the N-type non-doped layer 11 is a fourth TCO layer 12.
[0045] HBC cells are a type of solar cell that uses HJT's amorphous silicon thin film technology to create an interdigitated back contact cell (IBC) structure. Its structural features include no metal electrode blocking the front side, and a cross-arrangement of the P and N regions on the back side. HBC cells combine HJT and IBC technologies and have the characteristics of high short-circuit current and open-circuit voltage.
[0046] Specifically, the crystalline silicon substrate 1 is used as the basic material of the battery to absorb sunlight and generate current. On the one hand, the TCO layer 12 / composite TCO layer 13 allows light to pass through and enter the absorption layer of the silicon wafer, thereby improving the light absorption efficiency of the battery; on the other hand, it can conduct the collected current and transmit it to the external circuit. The main function of the anti-reflection layer 4 is to reduce light reflection and thus improve light absorption efficiency. By adding an anti-reflection layer to the front of the battery, the reflection of light on the surface of the silicon wafer can be reduced, allowing more light to enter the interior of the silicon wafer and be absorbed. In this way, the photoelectric conversion efficiency of the battery can be improved, thereby improving the performance of the battery. The functions of the front intrinsic hydrogenated amorphous silicon layer 3 and the back intrinsic hydrogenated amorphous silicon layer 5 are mainly reflected in three aspects: 1. Passivation: The intrinsic hydrogenated amorphous silicon layer can passivate the surface of the silicon wafer, reduce the surface recombination rate, and thus improve the minority carrier life; 2. Light trapping: This layer can form a pyramid velvet structure, reduce surface reflection, and increase the residence time of light on the surface of the silicon wafer, thereby improving the utilization rate of photons; 3. Increase the open circuit voltage: Since this layer has a good passivation effect, it ensures that the battery has a high open circuit voltage. The main function of the front velvet 2 is to improve the light absorption efficiency and passivate the surface of the crystalline silicon substrate 1. By forming a velvet structure, the scattering and reflection of light on the surface of the crystalline silicon substrate 1 can be increased, so that more light enters the interior of the crystalline silicon substrate 1 and is absorbed. At the same time, the velvet structure can also provide a larger surface area, making the surface of the crystalline silicon substrate 1 rougher, which is conducive to improving the passivation effect. The passivation effect can reduce the surface recombination rate, thereby increasing the minority carrier life and further improving the photoelectric conversion efficiency of the battery. Therefore, the front velvet surface 2 plays an important optimization role in the HBC battery, helping to improve the photoelectric performance and stability of the battery.
[0047] The present application also provides a method for preparing the above solar cell, the specific process comprising the following steps: (1) Select an N-type single crystal silicon wafer substrate for texturing and cleaning.
[0048] (2) Plasma enhanced chemical vapor deposition (PECVD) is used to deposit an intrinsic hydrogenated amorphous silicon layer on the front and back sides of a single crystal silicon substrate, and then an anti-reflection layer is deposited on the front intrinsic hydrogenated amorphous silicon, and a P-type doped microcrystalline silicon layer is deposited on the back intrinsic hydrogenated amorphous silicon. The SnO2 planar target is sputtered by physical vapor deposition (PVD) to obtain a SnO2 x During the sputtering process, argon, oxygen and argon-hydrogen mixed gas are used as process gases, and SnO x The mask layer is prepared in the same way as the TCO layer in the subsequent steps. x The mask layer is also the first TCO layer above the P-type doped microcrystalline silicon layer in the entire cell structure.
[0049] (3) Laser etching of SnOx The mask layer and the P-type doped microcrystalline silicon layer are formed by sputtering the SnO2 planar target using the PVD method to obtain the N-type non-doped layer and the fourth TCO layer. The second TCO layer and the third TCO layer are formed on the first TCO layer in sequence by sputtering the SnO2 planar target using the PVD method. Argon, oxygen and argon-hydrogen mixed gas are introduced as process gases during the sputtering process. Among them, when depositing the N-type non-doped layer and the second TCO layer, the oxygen flow rate is low to create more oxygen vacancies and generate more carriers, thereby reducing the work function and enhancing its ability to extract carriers; when preparing the fourth TCO layer and the third TCO layer, the oxygen flow rate is large, the oxygen vacancies are small, and the carrier concentration is low, which can reduce its parasitic absorption of incident light and increase its light transmittance.
[0050] (4) Use an etching solution to wash away the TCO above the P-type doped microcrystalline silicon layer away from the crystalline silicon substrate, so that the surface of the composite TCO layer is flat and the thickness is 100-110 nm.
[0051] (5) Copper electrodes are directly deposited on the surface of the TCO layer by electroplating to improve the interface contact between the electrode and TCO and reduce the contact resistance.
[0052] (6) Using laser etching, an insulating region is prepared between a region of the P-type doped microcrystalline silicon layer and a region of the N-type non-doped layer, and the width of the P-type doped microcrystalline silicon layer and the N-type non-doped layer is 3:1.
[0053] The present application also provides a solar cell assembly, which includes the above-mentioned solar cell.
[0054] The effect of the technical solution of this application is further explained below through specific examples.
[0055] Example 1 The following HBC cell was prepared according to the above-mentioned method for preparing a solar cell.
[0056] like Figure 2 As shown, the HBC cell in this embodiment includes: an anti-reflection layer 4, a front intrinsic hydrogenated amorphous silicon layer 3, a front velvet surface 2, a crystalline silicon substrate 1, a back intrinsic hydrogenated amorphous silicon layer 5, a P-type doped microcrystalline silicon layer 6, an N-type non-doped layer 11, a fourth TCO layer 12, a composite TCO layer 13 (including a first TCO layer 7, a second TCO layer 8 and a third TCO layer 9) and a metal electrode layer 10.
[0057] The anti-reflection layer 4 is MgF2 with a thickness of 150nm; the front intrinsic hydrogenated amorphous silicon layer 13 is amorphous silicon (non-doped) material with a thickness of 5nm; the crystalline silicon substrate 1 is an N-type single crystal silicon wafer with a thickness of 120μm; the back intrinsic hydrogenated amorphous silicon layer 5 is amorphous silicon (non-doped) material with a thickness of 5nm; the P-type doped microcrystalline silicon layer 6 is boron-doped microcrystalline silicon with a thickness of 20nm; the N-type non-doped layer 11 is SnO 1.65 , with a thickness of 20 nm; the fourth TCO layer 12 is SnO 1.8 , with a thickness of 110 nm; the first TCO layer 7 is SnO 1.8 , with a thickness of 40nm; the second TCO layer 8 is SnO 1.65 , with a thickness of 20 nm; the third TCO layer 9 is SnO 1.8 , with a thickness of 50nm; the metal electrode layer 10 is a copper electrode with a thickness of 15μm.
[0058] Comparative Example 1 The structure of Comparative Example 1 is basically the same as that of Example 1, except that the composite TCO layer 13 in Example 1 is a non-composite structure here, that is, a single-layer TCO layer is formed between the P-type doped microcrystalline silicon layer and the metal electrode layer, and the single-layer TCO layer is SnO 1.9 , with a thickness of 110 nm; in addition, the N-type non-doped layer 11 is SnO 1.71 , with a thickness of 20 nm; the fourth TCO layer 12 is SnO 1.9 , with a thickness of 110nm.
[0059] Performance Testing (1) Current density-voltage characteristic curve (JV) test The JV equipment was used to test the device performance. The specific parameters are shown in Table 1.
[0060] Table 1
[0061] The above test results show that the cell efficiency of Example 1 is significantly improved compared with that of Comparative Example 1. The solar cell with a composite TCO layer structure not only ensures light transmission performance, but also improves electrical conductivity, thereby generally improving the photoelectric conversion capacity of the solar cell.
[0062] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A solar cell, characterized in that: The solar cell comprises a back intrinsic hydrogenated amorphous silicon layer and a doped layer arranged in sequence, the doped layer comprises a P-type doped microcrystalline silicon layer and an N-type non-doped layer arranged alternately and spaced apart, and the surfaces of the P-type doped microcrystalline silicon layer and the N-type non-doped layer are independently and sequentially stacked with a TCO layer and a metal electrode layer; wherein the TCO layer on the surface of the P-type doped microcrystalline silicon layer is a composite TCO layer, and the composite TCO layer comprises a first TCO layer and a second TCO layer. The first TCO layer is close to the P-type doped microcrystalline silicon layer, and the first TCO layer and the second TCO layer have different light transmittance and resistivity.
2. The solar cell according to claim 1, characterized in that The light transmittance of the first TCO layer is greater than the light transmittance of the second TCO layer; and the resistivity of the first TCO layer is greater than the resistivity of the second TCO layer.
3. The solar cell according to claim 1, characterized in that The thickness of the composite TCO layer is 80-120 nm.
4. The solar cell according to claim 1, characterized in that The composite TCO layer further includes a third TCO layer, and the first TCO layer, the second TCO layer and the third TCO layer are stacked in sequence.
5. The solar cell according to claim 4, characterized in that: The thickness of the first TCO layer is 15-30 nm, the thickness of the second TCO layer is 5-20 nm, and the thickness of the third TCO layer is 30-100 nm.
6. The solar cell according to claim 4, characterized in that: The thickness ratio of the first TCO layer, the second TCO layer and the third TCO layer is (0.15-1):(0.05-0.67):
1.
7. The solar cell according to claim 4, characterized in that: The light transmittance of the first TCO layer is 85-92%, the light transmittance of the second TCO layer is 80-85%, and the light transmittance of the third TCO layer is 85-92%.
8. The solar cell according to claim 4, characterized in that: The resistivity of the first TCO layer is (3-5)×10 -3 Ω·cm, the resistivity of the second TCO layer is 8×10 -4 -3×10 -3 Ω·cm, The resistivity of the third TCO layer is (3-5)×10 -3 Ω·cm.
9. The solar cell according to claim 4, characterized in that: The first TCO layer, the second TCO layer and the third TCO layer each independently include one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3.
10. The solar cell according to claim 4, characterized in that: The first TCO layer and the third TCO layer include SnOx, wherein x is 1.75-1.85; The second TCO layer includes SnOx, wherein x is 1.6-1.
7.
11. The solar cell according to claim 1, characterized in that: The TCO layer on the surface of the N-type non-doped layer is a fourth TCO layer, and the thickness of the fourth TCO layer is 80-120 nm.
12. The solar cell according to claim 11, characterized in that: The fourth TCO layer has a light transmittance of 85-92% and a resistivity of (3-5)×10 -3 Ω·cm.
13. The solar cell according to claim 11, characterized in that: The fourth TCO layer includes one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3.
14. The solar cell according to claim 13, characterized in that: The fourth TCO layer includes SnOx, wherein x is 1.75-1.
85.
15. The solar cell according to claim 1, characterized in that The N-type non-doped layer includes one or more of SnOx, TiOx, LiFx, MgOx, and CsCO3.
16. The solar cell according to claim 15, characterized in that: The N-type non-doped layer includes SnOx, wherein x is 1.6-1.
7.
17. The solar cell according to claim 1, characterized in that The solar cell includes a crystalline silicon substrate, which includes a back side and a front side that are arranged opposite to each other. The back side is provided with the back side intrinsic hydrogenated amorphous silicon layer, and the front side is sequentially stacked with a front side velvet surface, a front side intrinsic hydrogenated amorphous silicon layer, and an anti-reflection layer, and the front side velvet surface is close to the front side.
18. A solar cell module, characterized in that: A solar cell comprising the solar cell described in any one of claims 1 to 17.